Phenotypic and Molecular Characterization of Extended-Spectrum Beta-Lactamase Producing Escherichia coli from Poultry - Barad, DB; Purohit, JH; Javia, BB; Savsani, HH; Mathapati, BS; Ghadosaria, SN; Kalariya, VA; Patel, JS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was undertaken with the objective of phenotypic and molecular characterization of extended-spectrum betalactamase (ESBL) producing E. coli isolates from poultry. A total of 300 cloacal swabs were collected, i.e., 200 from layer birds and100 from broiler birds from three different farms in and around Junagadh district of Gujarat state. Out of 300 samples, 126 (42.00%)samples yielded E. coli. These isolates belonged to layer 85 (42.50%) and broiler 41 (41.00%) birds. Out of 126 isolates, 27 (21.43%) wereconfirmed as ESBL producers, i.e., 19 (22.35%) and 8 (19.51%) from layer and broiler birds, respectively, by initial screening of isolatesfor their susceptibility to any of the third and fourth generation cephalosporins or monobactam antibiotics by disc diffusion methodand further confirmation by combination disc method using ESBL identification kits. Out of 27 phenotypically confirmed ESBL E. coliisolates blaTEM was detected in 21 (77.78%) and blaAmpC was detected in 15 (55.56%) isolates, while all the 27 isolates were foundnegative for the presence of blaSHV and blaCTXM genes. All the 27 isolates were found positive for either blaTEM or blaAmpC gene.Nine (33.33%) out of 27 isolates were found positive for both blaTEM and blaAmpC genes. The findings warrant the need for more strictregulations for usage of antibiotics in veterinary practices in order to prevent the emergence and dissemination of multidrug resistantE. coli pathogens among birds, animals, and humans.
Keywords: Extended-spectrum beta-lactamase; Escherichia col; blaTEM; blaCTXM; blaSHV; blaAmpC; Phenotypic characterization